Estimation of Therapeutic Potential of Fetal Liver Cryopreserved Cells in Model of Experimental Autoimmune Thyroiditis - Gladkikh, D. P.; Goltsev, A. N. (Problems of Cryobiology and Cryomedicine, 2009)
In experimental model of autoimmune thyroiditis a therapeutic efficiency of native and cryopreserved fetal liver cells (FLCs) was demonstrated. The advantages and possible mechanisms of therapeutic effect of fetoplacental complex preparations and FLCs, in particular, were envisaged.